Customer Stratification for an Industrial Distributor With a Service and Repair Business. Issue 1 (2nd January 2016) - Fowler, Andy; Natarajarathinam, Malini; Patwari, Krishna
Abstract: Customer purchasing behavior is not unique. Complex costs to serve make it difficult to manage customers, especially today, when businesses are offering more value-added services. This research study develops a methodology to allow companies with a service or repair component to segment customers, as well as manage relationships and growth. This methodology differs from existing ones by allowing companies to include the full profit contribution derived from billed labor into the customer profitability calculation. By accurately identifying profitability of individual customers, this methodology yields results that are more pragmatic for managers.